The Wiley-Blackwell Handbook of Addiction Psychopharmacology - MacKillop, James (Wiley, 2013)
"Much of our scientific efforts in tackling the multifactorial nature of addiction have taken place within individual disciplines, however it has become increasingly clear that the complexity of addiction requires an integrated approach. This handbook is timely and exceptional, intelligently combining the latest research approaches to understanding and tackling the prodigious public health burden of addiction. An authoritative resource, it establishes a comprehensive framework that will guide the field in the next era of addiction research."-John F. Kelly, Ph.D., President Elect, Society of Addiction Psychology, American Psychological Association; Associate Professor in Psychiatry, Harvard Medical School; Director, Addiction Recovery Management Service, Massachusetts General Hospital